COGNITIVE-MEANINGFUL OF FOREIGN LANGUAGE TEACHERS’ MORAL ATTITUDE: COMPARATIVE ASPECT - Kriaučiūnienė, Roma (Acta Paedagogica Vilnensia, 2011)
The article deals with the research into cognitive-meaningful level of moral attitudes of students and teachers of foreign languages. Lithuanian and foreign researchers acknowledge the fact that value attitudes alongside knowledge and skills as well as personal qualities of teachers are one of the most important components of teachers’ professional competence. The article raises the research problem what moral attitudes are particular to foreign language students and teachers working at schools and higher educational institutions and what moral values they acknowledge. The aim of the article is to present and compare the cognitive-meaningful level of moral attitudes of foreign language students and teachers. The research is based on the three-component attitude model, aiming at receiving a greater insight into the content of each separate component. The results of the analysis of the cognitive-meaningful component of foreign language students and teachers’ moral attitudes show that foreign language students and teachers demonstrated to have a mature level of cognitive-meaningful level of moral attitude. Although the respondents showed a very high acknowledgment of the importance of moral values, the understanding of the meaningfullness of these moral values is not very deep. Besides, the comparative analysis of the results of the reseach also revealed that teachers of foreign languages considered moral values to be less important and demonstrated a lower level of understanding of their meaningfullness than students of foreign languages. The conclusion is made that such level of cognitive-meaningful level of moral attitude of foreign language students and teachers might hinder the fulfilment of their responsibilities in their professional areas and might be a hindrance in the development of moral attitudes of their schoolchildren.